Tissue Tolerance Coupled With Ionic Discrimination Can Potentially Minimize the Energy Cost of Salinity Tolerance in Rice - Chakraborty, Koushik; Mondal, Subhankar; Ray, Soham; Samal, Pankajini; Pradhan, Bhubaneswar; Chattopadhyay, Krishnendu; Kar, Meera Kumari; Swain, Padmini; Sarkar, Ramani K. (Frontiers in Plant Science, 2020)
Salinity is one of the major constraints in rice production. To date, development of salt-tolerant rice cultivar is primarily focused on salt-exclusion strategies, which incur greater energy cost. The present study aimed to evaluate a balancing strategy of ionic discrimination vis-à-vis tissue tolerance, which could potentially minimize the energy cost of salt tolerance in rice. Four rice genotypes, viz., FL478, IR29, Kamini, and AC847, were grown hydroponically and subjected to salt stress equivalent to 12 dS m–1 at early vegetative stage. Different physiological observations (leaf chlorophyll content, chlorophyll fluorescence traits, and tissue Na+ and K+ content) and visual scoring suggested a superior Na+-partitioning strategy operating in FL478. A very low tissue Na+/K+ ratio in the leaves of FL478 after 7 days of stress hinted the existence of selective ion transport mechanism in this genotype. On the contrary, Kamini, an equally salt-tolerant genotype, was found to possess a higher leaf Na+/K+ ratio than does FL478 under similar stress condition. Salt-induced expression of different Na+ and K+ transporters indicated significant upregulation of SOS, HKT, NHX, and HAK groups of transporters in both leaves and roots of FL478, followed by Kamini. The expression of plasma membrane and vacuolar H+ pumps (OsAHA1, OsAHA7, and OsV-ATPase) were also upregulated in these two genotypes. On the other hand, IR29 and AC847 showed greater salt susceptibility owing to excess upward transport of Na+ and eventually died within a few days of stress imposition. But in the “leaf clip” assay, it was found that both IR29 and Kamini had high tissue-tolerance and chlorophyll-retention abilities. On the contrary, FL478, although having higher ionic-discrimination ability, showed the least degree of tissue tolerance as evident from the LC50 score (amount of Na+ required to reduce the initial chlorophyll content to half) of 336 mmol g–1 as against 459 and 424 mmol g–1 for IR29 and Kamini, respectively. Overall, the present study indicated that two components (ionic selectivity and tissue tolerance) of salt tolerance mechanism are distinct in rice. Unique genotypes like Kamini could effectively balance both of these strategies to achieve considerable salt tolerance, perhaps with lesser energy cost.